KEANEKARAGAMAN MIKROALGA DI PERAIRAN PANTAI CEMARA DESA LEMBAR SELATAN KECAMATAN LEMBAR KABUPATEN LOMBOK BARAT - Subagio Subagio (Bioscientist : Jurnal Ilmiah Biologi, 2016)
ABSTRACT: Microalgae is the most primitive cell-sized plant form known as the phytoplankton, where this phytoplankton is one of marine biota which has a vital role for a waters because as primary producer for water. Where in this study will be taken 3 stations, station 1 is close to the resident's house, the station 2 transport lines and station 3 is in the middle of the waters of Cemara Beach. The purpose of this study were (1) To know the species of microalgae species located on the beach Cemara. (2) To know the diversity, uniformity and dominance of microalgae at Cemara beach as the basis for the preparation of Cryptogamae Systematic practice manual. (3) To find out the results of research can be used as the basis for the preparation of Cryptogamae Systematic practice manual. The type of research used in this study is descriptive. The data obtained in this study is qualitative data analyzed descriptively. Calculated index of species diversity, uniformity, and dominance, using Shannon Wiener's formula. The results showed that (1) Indices of diversity of microalgae in Cemara Coast waters at each station, station I (2.19), station II (2.44), and station III (1.71) which means that the three stations have community moderate biota or moderately polluted water quality. (2) Uniformity index of microalgae at each station, station I (0,62), station II (0,69), station III (0,48) which means in all three stations have uniformity of organism in balance condition. (3) The dominant index of microalgae at each station is obtained an index of average dominance of 1, there are species that dominate other species or unstable community structure. The conclusion of this research is the diversity of microalgae in the waters of Pantai Cemara Desa Lembar Selatan Lembar subdistrict, West Lombok regency has index of medium contaminated diversity, uniformity index and unstable dominance index.